Antidiabetic, antihyperlipidemic and antioxidant influences of the spice cinnamon ( Cinnamomum zeylanicumon ) in experimental rats - Raja Serairi Beji; Sameh Khemir; Wissem Aidi Wannes; Khaoula Ayari; Riadh Ksouri (Universidade de São Paulo, 2018)
ABSTRACT The present study investigates the effect of cinnamon (Cinnamomum zeylanicumon) powder supplementation on glucose levels, lipid profiles, and oxidative stress parameters in alloxan-induced diabetic rats. Diabetes was induced in adult male Wistar rats via a single subcutaneous alloxan injection (15 mg/kg). Cinnamon powder was mixed with the standard feed of the rats in an amount of 5% for 28 consecutive days. Serum concentrations of total cholesterol (TC) and triglycerides (TG) were assayed at the end of the experimental period in all investigated groups. Anti-oxidative enzymes such as glutathione peroxidase (GPx), catalase (CAT) and superoxide dismutase (SOD) were sought in the serum and pancreas. Alloxan caused the fasting blood sugar level to increase. The administration of cinnamon blocked the increase of blood glucose. There was also a significant difference in the TG and TC levels between control and treated diabetic rats. In diabetic rats, cinnamon treatment restored the activities of SOD, CAT and GPx. These findings suggested that cinnamon has an anti-hyperglycemic effect, improves lipid profiles, and protect against damage induced by oxidative stress in the diabetic state.